2017
DOI: 10.1111/ejn.13729
|View full text |Cite
|
Sign up to set email alerts
|

Increasing motor cortex plasticity with spaced paired associative stimulation at different intervals in older adults

Abstract: The ability of priming non-invasive brain stimulation (NIBS) to modulate neuroplasticity induction (i.e. metaplasticity) within primary motor cortex (M1) may be altered in older adults. Previous studies in young subjects suggest that consecutive NIBS protocols interact in a time-dependent manner and involve homoeostatic metaplasticity mechanisms. This was investigated in older adults by assessing the response to consecutive blocks of paired-associative stimulation (PAS) separated by different inter-PAS interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…These results highlight the importance of timing for “priming” stimulation in facilitating motor skill learning (Fig. 4E), consistent with studies using TMS and transcranial electrical stimulation (TES) for M1 priming stimulation to improve subsequent motor skill acquisition ( 52 ). To rule out the possibility that the reduced success rate in the contralateral cTBUS group was due to reduced motor activity, similar to the case of motor cortex injury ( 53 ), we examined the number of reaching attempts per minute.…”
Section: Resultssupporting
confidence: 87%
“…These results highlight the importance of timing for “priming” stimulation in facilitating motor skill learning (Fig. 4E), consistent with studies using TMS and transcranial electrical stimulation (TES) for M1 priming stimulation to improve subsequent motor skill acquisition ( 52 ). To rule out the possibility that the reduced success rate in the contralateral cTBUS group was due to reduced motor activity, similar to the case of motor cortex injury ( 53 ), we examined the number of reaching attempts per minute.…”
Section: Resultssupporting
confidence: 87%
“…Consistent with the BCM theory, studies exploring homeostatic plasticity using repetitive tetanic stimulation [ 5 , 33 35 ] and noninvasive brain stimulation [ 3 , 4 , 36 38 ] have shown that neuronal activity is modified based on the level of postsynaptic activity [ 39 41 ]. For example, studies have shown that two blocks of anodal tDCS produce effects on M1 that follow a time-dependent rule consistent with homeostatic mechanisms [ 9 ].…”
Section: Discussionmentioning
confidence: 98%
“…These markings were continuously monitored throughout the protocol. Active motor threshold (AMT) was defined as the lowest TMS stimulus intensity necessary to elicit a MEP discernible from background EMG signal in 3 out of 5 trials (Sidhu et al, 2017). TMS intensity was set at 120 % of AMT for all measurement blocks (55 ± 10 % of maximum stimulator output) to ensure effective activation of the FDI during the experiment.…”
Section: Methodsmentioning
confidence: 99%